Improvements on a laser scattering technique for droplet size measurements applied to a gas-liquid separation equipment - Marchetti, Jorge Mario (2011)
The knowledge of droplet size distributions in a gas-liquid separation equipment is of high relevance due to the importance of removal efficiency in these systems. Different techniques could be used to measure droplet size, being one of them the diffraction of a laser beam. The laser is located behind glasses, being the formation of droplets on the glasses one of the main problems encountered when using this technique. Due to this major problem, different innovative solutions have been proposed and implemented to the gas-liquid separation column in order to obtain satisfactory results. A shutter mechanism, a purge gas and combination of these two solutions were tested. It was shown that the modified technique is suitable for liquid droplet measurements under ambient conditions. It has been also shown that the combination of these two solutions reduced considerably the amount of droplets that interacts with the glasses, allowing getting better data.